2020
DOI: 10.1002/jbm4.10446
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Antiretroviral Therapy‐Naïve HIV‐1–Infected Young Adult ‐Women Using Depot Medroxyprogesterone Acetate or Nonhormonal Contraceptives in Uganda

Abstract: Most studies evaluating BMD in human immunodeficiency virus (HIV)‐infected populations have focused on antiretroviral therapy (ART)‐experienced patients. In this study, the association between HIV‐1 and/or depot medroxyprogesterone acetate (DMPA) and BMD among untreated HIV‐1–infected women in a resource‐limited setting was assessed before long‐term exposure to ART. The data were then compared with that of the 2005–2008 United States National Health and Nutrition Examination Survey data for non‐Hispanic White … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…77 A recent study from Kampala, Uganda, in East Africa, comparing the BMD of premenopausal Black women with the NHANES reference database, found that mean lumbar spine BMD was 1.2 SD below the mean for U.S. Black women and 0.8 SD below that of U.S. white women, while at the femoral neck, the BMD was 0.4 SD below that of U.S. Black women but 0.1 SD above that of U.S. white women. 78 In West Africa, a study of pre and postmenopausal Gambian women revealed that after correcting for age, weight, and height, bone mineral content at the lumbar spine was on average 24% lower than that of white women in the UK. The reduction in bone mineral content increased to 42% in those >64 years of age.…”
Section: Regional Considerations High-income Countriesmentioning
confidence: 99%
“…77 A recent study from Kampala, Uganda, in East Africa, comparing the BMD of premenopausal Black women with the NHANES reference database, found that mean lumbar spine BMD was 1.2 SD below the mean for U.S. Black women and 0.8 SD below that of U.S. white women, while at the femoral neck, the BMD was 0.4 SD below that of U.S. Black women but 0.1 SD above that of U.S. white women. 78 In West Africa, a study of pre and postmenopausal Gambian women revealed that after correcting for age, weight, and height, bone mineral content at the lumbar spine was on average 24% lower than that of white women in the UK. The reduction in bone mineral content increased to 42% in those >64 years of age.…”
Section: Regional Considerations High-income Countriesmentioning
confidence: 99%
“… 15 Indeed in our baseline analysis, we observed lower BMD among ART-naive current DMPA-IM users compared with previous users and non-users. 18 Similar to the mechanism of TDF-associated BMD loss, studies of bone turnover in DMPA-IM users have suggested that the effects of DMPA-IM on the skeleton are at least partially mediated through increased bone resorption and reduced formation. 23 , 24 Although we only obtained incomplete data (6 months rather than 2 years) on BMD loss among women living with HIV using DMPA-IM before ART initiation, we demonstrate significant declines in BMD in this group compared with the control group without HIV at the lumbar spine at 24 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of their HIV infection status, women were excluded if they had been pregnant or breastfeeding in the past 6 months before enrolment, had intented to become pregnant during the 2-year study, or had a pre-existing medical condition known to affect bone metabolism. 18 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations